Psychological Well-Being (PWB) of School Adolescents Aged 12-18 yr, its Correlation with General Levels of Physical Activity (PA) and Socio-Demographic Factors In Gilgit, Pakistan - Yasmin KHAN; Muhammad Hussain TAGHDISI; Keramat NOURIJELYANI (Tehran University of Medical Sciences, 2015)
Background: Adolescence is a critical developmental stage marked by complex transitions. The purpose of study was to assess school adolescents' PWB, examine the relationship of PA and socio-demographic factors with PWB. Methods: A cross sectional study conducted in five randomly selected schools with 345 adolescents (aged 12-18) from grade 6th-10th. A self-administered Well-Being index was adapted to measure PWB and questionnaire for adoles-cents PA (PAQ-A). Socio-demographic variables determined: age, gender, household income and parental education. Bivariate and multivariate regression analyses performed to examine the association between PWB, PA and covariates. Results: Findings indicated the mean age 14.64 (SD=1.275), 55.4% were female. Without gender difference the ma-jority (43.4%) of adolescents showed moderate, while (23.2%) revealed low level of PWB. Participants with low level likely to have depression but scores were significantly not different between low, moderate and high PWB with PA. Socio-demographic trends of adolescents' were observed significant (P <0.005) for PWB. In multivariable analysis the mean wellbeing in females adjusted for other covariates was significant (P =0.004) than males. PWB importantly (P <0.001) decreased by 3.36 units as its covariates increased and PA score in boys found 0.05 unit more than girls. Conclusion: The study results are invaluable in addressing low, moderate and high levels of PWB. Inadequate PA and PWB decreasing with some socio-demographic covariates is crucial health issue among female adolescents in Pakistan. Further studies need to find barrier, social indicators of PWB and implication of health among adolescents.